Islamic Educational Thoughts of Tuan Guru Haji (TGH) Muhammad Sholeh Chambali (Tuan Guru Bengkel) - Segaf Baharun (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2022)
In every era, there are phenomenal events that impress people, full of astonishment and awe. In this context, admiration can be for objects, animals, or people so that it is referred to as